Performance Evaluation of Permanent and Part-Time Faculty in the University of Eastern Philippines - Legaspi, Korina P (International journal of innovation and applied studies, 2015)
This study aims to determine the performance evaluation of permanent and part-time faculty as rated by students and supervisors in the University of Eastern Philippines. A descriptive comparative study was used. There were a total of 250 subjects for this study, 210 were permanent faculty members and 40 were part-time lecturers of the University of Eastern Philippines. The respondents were taken from the total population using the stratified sampling method and were randomly selected. A descriptive-comparative survey research design was used in this study. Findings of this study showed that there is a significant difference in the performance of part-time and permanent faculty as rated by supervisors but findings showed no significant difference in the performance as perceived by the students. This reaffirms the theory of Bandura (1989) that employees perform their obligations as mandated by their position. Further, since part-time lecturers are not expected to perform research, extension and production, then they did not perform well in those areas.